Myomedin replicas of gp120 V3 loop glycan epitopes recognized by PGT121 and PGT126 antibodies as non-cognate antigens for stimulation of HIV-1 broadly neutralizing antibodies - Daniel Lišková, Veronika; Kosztyu, Petr; Kuchař, Milan; Černý, Jiří; Bharadwaj, Shiv; Petroková, Hana; Vroblová, Eliška; Křupka, Michal; Malý, Michal; Zosinčuková, Tereza; Šulc, Josef; Rašková Kafková, Leona; et al. (Frontiers in immunology, 2022)
INTRODUCTION: Imprinting broadly neutralizing antibody (bNAb) paratopes by shape complementary protein mimotopes represents a potential alternative for developing vaccine immunogens. This approach, designated as a Non-Cognate Ligand Strategy (NCLS), has recently been used for the identification of protein variants mimicking CD4 binding region epitope or membrane proximal external region (MPER) epitope of HIV-1 envelope (Env) glycoprotein. However, the potential of small binding proteins to mimic viral glycan-containing epitopes has not yet been verified. METHODS: In this work, we employed a highly complex combinatorial Myomedin scaffold library to identify variants recognizing paratopes of super candidate bNAbs, PGT121 and PGT126, specific for HIV-1 V3 loop epitopes. RESULTS: In the collection of Myomedins called MLD variants targeted to PGT121, three candidates competed with gp120 for binding to this bNAb in ELISA, thus suggesting an overlapping binding site and epitope-mimicking potential. Myomedins targeted to PGT126 designated MLB also provided variants that competed with gp120. Immunization of mice with MLB or MLD binders resulted in the production of anti-gp120 and -Env serum antibodies. Mouse hyper-immune sera elicited with MLB036, MLB041, MLB049, and MLD108 moderately neutralized 8-to-10 of 22 tested HIV-1-pseudotyped viruses of A, B, and C clades in vitro. DISCUSSION: Our data demonstrate that Myomedin-derived variants can mimic particular V3 glycan epitopes of prominent anti-HIV-1 bNAbs, ascertain the potential of particular glycans controlling neutralizing sensitivity of individual HIV-1 pseudoviruses, and represent promising prophylactic candidates for HIV-1 vaccine development.
Keywords: glycoprotein 120; neutralizující protilátky; polysacharidy; HIV-1; protein scaffold; Mice; HIV Antibodies; protein engineering; vaccine; Antibodies, Neutralizing; Animals; HIV Envelope Protein gp120; zvířata; široce neutralizující protilátky; myši; HIV obalový protein gp120; Polysaccharides; Epitopes; broadly neutralizing antibody; HIV protilátky; epitopy; Broadly Neutralizing Antibodies